HIGH SCHOOL LEARNERS’ PERCEPTIONS OF THEIR STAD COOPERATIVE LEARNING EXPERIENCE IN STUDYING CONDITIONAL SENTENCES: DO GENDER AND PAST ACHIEVEMENT MATTER? - Pramastiwi, Priska (Journal of English Department WM, 2014)
Cooperative Learning (CL) is notably superior among other instructional learning methods in improving academic achievement and affective domains. Nevertheless, how learners think of the enjoyableness of CL and the circumstances that heighten such positive learning outcomes are often neglected. This research explored the perceptions of 36 high school learners who studied the functions and patterns of the notoriously problematic Conditional Sentences within the dynamics of a CL technique called Student Teams Achievement Division (STAD). It examined the extent to which learners perceived their amount of learning, their contributions to the learning of others and the overall pleasure of following the STAD cooperative strategy. As individual characteristics contribute to the success of CL applications, the perception between boys and girls, and high and low achievers were compared to ascertain any peculiarities. Confirmed through Chi-square analysis, the research uncovered that neither gender nor past achievement matter in the forming of perception as all participants perceived the learning process positively. However, males were slightly more appreciative on the importance of team contribution as well as individual accountability for their learning success. Only a small rate of lower-ability students felt strongly positive of improved comprehension. Likewise, surpassing their counterparts, high achievers more firmly verified the clarity of STAD concept. Both high and low achievers provided adequate contribution to the teamwork, yet only 25% of the entire population felt strongly about recommending STAD based on the unlikeliness for non-conceptual learning to fit with the approach.